Etched Polymer Fibre Bragg Gratings and Their Biomedical Sensing Applications - Ginu Rajan; Kishore Bhowmik; Jiangtao Xi; Gang-Ding Peng (Sensors, 2017)
Bragg gratings in etched polymer fibres and their unique properties and characteristics are discussed in this paper. Due to the change in material and mechanical properties of the polymer fibre through etching, Bragg gratings inscribed in such fibres show high reflectivity and enhanced intrinsic sensitivity towards strain, temperature, and pressure. The short-term and long-term stability of the gratings and the effect of hysteresis on the dynamic characteristics are also discussed. The unique properties and enhanced intrinsic sensitivity of etched polymer fibre Bragg grating are ideal for the development of high-sensitivity sensors for biomedical applications. To demonstrate their biomedical sensing capabilities, a high-sensitivity pressure transducer that operates in the blood pressure range, and a breathing rate monitoring device are developed and presented.